PENGEMBANGAN MEDIA BUKU CERITA BERGAMBAR UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SEKOLAH DASAR - Sitorus, Michael; Misbah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low motivation of students to learn Indonesian, schools focus more on textbooks. This research aims to develop a picture storybook learning media to increase students' learning motivation in Indonesian Language subjects. This research uses the Research and Development (R&D) method using the ADDIE model which consists of five stages, namely analysis, design, development, implementation and evaluation. The results of the study show that the media of illustrated storybooks is declared